Characteristic Features of Phonetic Labarotorias - Uktamovich, Marufov Elyor (Researchparks Publishing, 2023)
this article gives information about the phonetic laboratory, its types, practical and theoretical aspects, tasks, methods of using it, virtual learning of languages, social psycholinguistic features of oral speech.